National face to face training course on utilizing the Excel CLEANED tool for assessing the environmental impact of animal production - Mannai, Amal; Tebourbi, Ons; Frija, Aymen; Idoudi, Zied (International Center for Agricultural Research in the Dry Areas, 2023)
The report describes a training session on "Utilizing the Excel CLEANED Tool for Assessing the Environmental Impact of Animal Production" that took place in Tunisia in September 2023 organized by GIZ as part of the "Innovations for Agriculture and the Food Industry (IAAA)" project in partnership with ICARDA, a part of CGIAR's "Livestock and Climate" and "Agroecology" Initiatives. The training aimed to equip participants with the necessary skills to use the Excel CLEANED tool for data collection and scenario assessment. The specific outputs of the training include enhanced participant skills, validation of the tool's effectiveness, and a heightened awareness of the importance of proactive environmental measures in livestock production. The training's ultimate goal is to contribute to the establishment of a national database on the environmental impact of animal production, with a particular focus on dairy production, to help the Tunisian Ministry of Agriculture with strategic planning. The training was attended by 33 participants, including representatives from various sectors such as scientists, academic institutions, government, development sector agents, and development institutions.